2001
DOI: 10.1177/152660280100800109
|View full text |Cite
|
Sign up to set email alerts
|

Endoluminal Stent Placement and Coil Embolization for the Management of Carotid Artery Pseudoaneurysms

Abstract: Endovascular treatment of carotid artery pseudoaneurysms is a useful alternative to standard surgical repair. This modality avoids the necessity for surgical exposure at the skull base with its inherent morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0
5

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 19 publications
1
64
0
5
Order By: Relevance
“…Endovascular techniques such as coil embolization and stent placement have gained increasing popularity in the treatment of blunt vascular injuries including pseudoaneurysm, fistula, and flow-limiting dissections. While some studies have raised concerns over the safety of endovascular techniques as a result of increased risks of stroke and stent occlusion 17,27,34 , other groups have reported good longterm results with endovascular treatment [35][36][37][38] . Specifically, endovascular occlusion has been advocated as a feasible and safe treatment for traumatic vertebral arteriovenous fistula 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular techniques such as coil embolization and stent placement have gained increasing popularity in the treatment of blunt vascular injuries including pseudoaneurysm, fistula, and flow-limiting dissections. While some studies have raised concerns over the safety of endovascular techniques as a result of increased risks of stroke and stent occlusion 17,27,34 , other groups have reported good longterm results with endovascular treatment [35][36][37][38] . Specifically, endovascular occlusion has been advocated as a feasible and safe treatment for traumatic vertebral arteriovenous fistula 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular embolization techniques using detachable coils can be used for the treatment of pseudoaneurysms. However, wide-neck aneurysms such as our case are difficult to treat, mainly because the detached coils are prone to migrate or herniate into the parent arteries, 3,4,8,12,13) so a modification of the simple coil embolization technique is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoaneurysms have been successfully treated by coil embolization with stenting, enabling preservation of the patency of the parent vessels as well as obliteration of the aneurysm. 4,8,10,12,13) Most of these pseudoaneurysms were idiopathic, 10) or secondary to trauma or direct neurosurgical procedures. 4,8,12,13) Two cases of pseudoaneurysms of the vertebral arteries secondary to endovascular procedures were treated by coil embolization combined with stenting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bush et al 10 reported the treatment of ICA pseudoaneurysms due to blunt carotid injury by placing bare stents and adding coil embolization of the excluded pseudoaneurysm in 5 patients; occlusion of all 5 pseudoaneurysms resulted. At follow-up (mean, 11.7 months) all 5 pseudoaneurysms remained occluded, with 4 of 5 stents remaining widely patent; 1 of the 4 had developed a 60% focal stenosis.…”
Section: Discussionmentioning
confidence: 99%